MIGRATION PROCESSES AND QUALITY OF LIFE OF THE POPULATION IN THE CONDITIONS OF WAR - PETROVSKA, Anastasiia (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. The transition of the Russian-Ukrainian war into the phase of high intensity, which fell on February 24, 2022, became the cause of acute demographic and economic crises in Ukraine, mass forced migration. The processes to which the Ukrainian state was gradually able to adapt in the period 2014–2021 acquired catastrophic proportions in 2022 due to the fact that the entire country became the arena of military operations and destructive shelling. The consequences of Russia’s full-scale invasion of Ukraine will be felt even decades after its end. The war has already introduced a disproportion in the spatial distribution of the population, which may deepen in the future.Methods. Using the comparative and geographical method, statistical analysis and synthesis, the quantitative indicators of forced external and internal migration of the population due to the war in Ukraine were revealed, the level of quality of life of internally displaced persons, the amount of destruction due to full-scale invasion and permanent shelling of the Ukrainian territory was investigated. Ways to restore the destroyed territory, residential and non-residential infrastructure of the country are analyzed. With the help of a qualitative method of sociological research (in-depth interviews), the experience of displacement of external and internal migrants was investigated.Results. The subjective vision of internal and external migrants regarding the prospects of their return to their primary places of residence was determined, which directly depends on both the time spent outside their places of origin and whether refugees and internally displaced persons have a place to return to, as well as other traumatic factors.Conclusions. Reconstruction of the destroyed, overcoming the demographic crisis, well-thought-out housing and social policy for the integration of internally displaced persons and encouraging the return of external forced migrants – these are the challenges that are acutely facing Ukraine at the moment. Another important factor is that the disproportion, when the population is unevenly distributed, mainly in the western regions of Ukraine, may be present even after the war ends. Accession to the European Union, when those regions that are closer to the EU countries will be more developed, will deepen this skew.
Keywords: quality of life of the population; internally displaced persons; forced migration; cities; reconstruction